Psychological morbidity in Leber’s hereditary optic neuropathy depends on phenotypic, social, economic, and genetic factors - Finsterer J (Dove Medical Press, 2017)
Josef Finsterer,1 Sinda Zarrouk-Mahjoub2 1Krankenanstalt Rudolfstiftung, Vienna, Austria; 2University of Tunis El Manar, Genomics Platform, Pasteur Institute of Tunis, Tunis, Tunisia We have read with interest the article by Garcia et al1 about the effect of visual impairment on psychological well-being with regard to mood, interpersonal interactions, and career-related goals.1 Among the 103 Leber’s hereditary optic neuropathy (LHON) patients, half became depressed with negative impacts on interpersonal relations and career goals. At diagnosis, older age corresponded to higher depression prevalence than young age. We have the following comments and concerns.View the original paper by Garcia and colleagues.